Core-shell structured hierarchical Ni nanowires and NiS/Co3S4 microflowers arrays as a high-performance supercapacitor electrode. (January 2023) - Mahieddine, Abdelkadir; Adnane-Amara, Leila; Tebaa, Thinhinane; Saba, Cylia
Abstract: To develop new positive electrode materials with high electrochemical performance for practical applications in energy storage, the design of new complex morphologies with a core-shell structure based on MS sulfide materials with M = Ni, Co, Fe or Mn and nanomaterials metallic is a very essential technique. In this study, an asymmetric supercapacitor (ASC) with high energy density was fabricated by combining a NiS/Co3 S4 @h-Ni NWs battery-like electrode with α-MnO2 as a pseudo-capacitive electrode. Firstly, hierarchical Nickel Nanowires, h-Ni NWs, were prepared by the reduction of Ni 2+ ions by hydrazine, and then the h-Ni NWs are coated with NiS/Co3 S4 by the hydrothermal method to form a core-shell structure with good electrical conductivity. The electrochemical performance of the NiS/Co3 S4 @h-Ni NWs electrode was evaluated in the 4 M LiOH electrolyte. The results showed that the NiS/Co3 S4 @h-Ni NWs electrode had a specific capacity of 1893 C/g at a current density of 1 A/g and an excellent retention of 98.63 % of its initial specific capacity after 10, 000 charge-discharge cycles at 20 A/g due to the synergistic interaction between the nickel nanowires and (Ni/Co) sulfides in the developed core-shell structure. Furthermore, the fabricated ASC device provided a high energy density of 101.05 Wh/kg at a power density of 850 W/kg. At a maximum power density of 17 kW/kg, the device provided an energy density of 57.13 Wh/kg along with excellent capacity retention (83.56 %) after 10, 000 charge-discharge cycles at 20 A/g. Graphical abstract: Unlabelled Image Highlights: The core-shell structured hierarchical Ni nanowires and NiS/Co3 S4 microflowers was prepared the first time. NiS/Co3 S4 @h-Ni NWs exhibited a specific capacity of 1893 C/g at a current density of 1 A/g. NiS/Co3 S4 @h-Ni NWs// α-MnO2 ASC delivered a high energy density of 101.05 Wh/kg at the power density of 850 W/kg. The proposed mechanisms for improved supercapacitor performance were well analyzed and demonstrated.